Case Report: Opposite Effects of BRAF Inhibition on Closely Related Clonal Myeloid Disorders - Hostettler, Katrin E.; Casañas Quintana, Elisa; Tamm, Michael; Savic Prince, Spasenija; Sommer, Gregor; Chen, Wei-Chih; Nordmann, Thierry Michael; Lundberg, Pontus; Stehle, Gregor Thomas; Daikeler, Thomas (Frontiers in Oncology, 2021)
Langerhans cell histiocytosis (LCH) commonly co-occurs with additional myeloid malignancies. The introduction of targeted therapies, blocking ‘driver’ mutations (e.g. BRAF V600E), enabled long-term remission in patients with LCH. The effect of BRAF inhibition on the course and the prognosis of co-existing clonal hematopoiesis is poorly understood. We report on a 61-year-old patient with systemic (BRAF V600E positive) LCH and concomitant BRAF wild type (wt) clonal cytopenia of unknown significance (CCUS) with unfavorable somatic mutations including loss of function (LOF) in NF1. While manifestations of LCH improved after blocking BRAF by dabrafenib treatment, the BRAF wt CCUS progressed to acute myeloid leukemia (AML). The patient eventually underwent successful allogeneic hematopoietic stem cell transplantation (HSCT). We in depth analyzed the clonal relationship of CCUS and the tissue affected by LCH by using next generation sequencing (NGS). These findings suggest activation of the MAP kinase pathway in the CCUS clone due to the presence of the RAS deregulating NF1 mutation and wt BRAF, which is reportedly associated with paradoxical activation of CRAF and hence MEK. Patients with LCH should be carefully screened for potential additional clonal hematological diseases. NGS can help predicting outcome of the latter in case of BRAF inhibition. Blocking the MAP kinase pathway further downstream (e.g. by using MEK inhibitors) or allogeneic HSCT may be options for patients at risk.